Analysis of FOXL2 detects three novel mutations and an atypical phenotype of blepharophimosis‐ptosis‐epicanthus inversus syndrome. (1st July 2016) - Krepelova, Anna; Simandlova, Martina; Vlckova, Marketa; Kuthan, Pavel; Vincent, Andrea L; Liskova, Petra
Abstract: Background: Mutations in FOXL2 are known to cause autosomal dominant blepharophimosis‐ptosis‐epicanthus inversus syndrome (BPES), variably associated with premature ovarian failure. In this study, we report results of mutational screening in a Czech and Slovak patient population with BPES. Design: Case series. Participants: Thirteen probands of Czech and one proband of Slovak origin with BPES and their available family members. Methods: Sanger sequencing and multiplex ligation‐dependent probe amplification in 14 probands with BPES. Targeted mutational screening in first‐degree relatives. Main Outcome Measures: Genetic characterization and phenotype evaluation in Czech and Slovak individuals with BPES and their family members. Results: Eight different mutations were detected including three novel ones: c.5T>G; p.(Met2Arg), c.197C>A; p.(Ala66Glu) and c.701_702insTGCAGCCGCAGCGGCTGCAGCAGCTGCGGCTGCAGCCGC; p.(Ala222_Ala234dup). In one family, the molecular genetic cause of disease was not identified by the methodology used. In 13 pedigrees, a negative family history suggested a de novo origin, which could be confirmed by targeted mutational screening in four families. One 62‐year‐old female with the c.663_692dup30 mutation had an atypical phenotype presenting as moderate ptosis compensated by frontalis muscle contraction, no epicanthus inversus and no premature ovarian failure. Conclusions: The de novo mutation rate in FOXL2 is exceptionally high compared with other dominant disorders manifesting with an ocular phenotype. In cases reporting a negative family history, careful examination of both parents is important to exclude mild features of the BPES phenotype.